Bridging Teachers’ Views and Classroom Practices in Teaching English for Young Learners - Sari Diana; Tuti Hidayati (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
Teachers play a central role in shaping how English is taught to young learners in primary classrooms. This study investigates teachers’ views and classroom practices in teaching English for young learners in primary schools in Aceh. The study aims to understand how teachers perceive English instruction and how these views shape their classroom practices. A qualitative case study design was used. Data was collected through questionnaires, interviews, and classroom observations involving 23 primary school teachers. The findings show that teachers view English as an important but informally positioned subject. Although materials are available, many are not suitable for young learners, which leads teachers to create their own resources. Classroom practices emphasize repetition, songs, games, and play-based activities to maintain engagement and emotional safety. Teachers frequently adapt instruction through bilingual explanation and flexible classroom interaction. Differences in teaching practices were linked to teachers’ educational backgrounds. Despite the absence of a formal curriculum, English teaching continues through teacher initiative.